Antibacterial Co(II), Cu(II), Ni(II) and Zn(II) Complexes of Thiadiazoles Schiff Bases - Chohan, Zahid H. (Hindawi Publishing Corporation, 2001)
Schiff bases were obtained by condensation of 2-amino-l,3,4-thiadiazole with 5-substituted-salicylaldehydes which were further used to obtain complexes of the type [M(L)(2)]Cl(2), where M=Co(II), Cu(II), Ni(II) or Zn(II). The new compounds described here have been characterized by physical, spectral and analytical data, and have been screened for antibacterial activity against several bacterial strains such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The antibacterial potency of these Schiff bases increased upon chelation/complexation, against the tested bacterial species, opening new aproaches in the fight against antibiotic resistant strains.